THE POTENTIAL OF SECONDARY METABOLITES COMPOUNDS OF METHANOL EXTRACT STEM BARK MELOCHIA UMBELLATE AS ANTI-BACTERIAL - Usman -; Nunuk Hariani S; Hanapi Usman; Ahyar Ahmad (PROSIDING SEMINAR KIMIA, 2015)
A Study antibacterial essay of the methanol extracts of steam bark M.umbellate (Houtt) Stapf var. degrabrata (Paliasa). The results of this study showed that the methanol extract from the bark of M. umbellate (Houtt) Stapf var. degrabrata group of compounds containing alkaloids, flavonoids, triterpenoids, phenolics and saponins. Methanol extract from the bark of M. umbellate can inhibit the growth of bacteria Bacillus subtilis, Staphylococcus aureus, gram-negative bacteria as well as representing Escherichia coli, Salmonella thypi, and Pseudomonas aeruginosa representing gram-positive bacteria. At a concentration of 400 ppm of methanol extracts of these plants showed effective barrier against bacteria tested, with a zone of inhibition, respectively as follows: 12.67 mm against bacteria B. subtilis, 12.97 mm against bacteria, S. aureus, 11.86 mm against bacteria E. coli and 12.12 mm against bacteria S. thypi. However, methanol extract from the bark of